ANTESEDEN KOMITMEN ORGANISASI DAN MOTIVASI: KONSEKUENSINVA TERHADAP KINERJA AUDITOR INTERN PEMERINTAH - Marganingsih, Arywarti; Martani, Dwi (UI Scholars Hub, 2010)
The purpose of this study is to empirically investigate whether organizational culture, leadership style, and monetary incentive are antecedents of organizational commitments, while time budget pressure, task complexity, discussion of audit review, and organizational commitment are antecedents of motivation. This study also investigates the consequences of organizational commitment and motivation and their antecendents on auditors ‘performance. The study uses 276 internal auditors of Non Departemental Government Institutions as our respondents. The study uses Structural Equation Modelling that is run by LISREL. This study provides evidence that organizational culture is an antecedent of organizational commitment while discussion of audit review and organizational commitment are antecedents of motivation. This study finds that organizational commitment, motivation, time budget pressure and discussion of audit review have positive consequences on auditors ‘performance while organizational culture is found to have negative consequence on auditors ‘performance.